"Sworn" friends: Russia and Germany in M. Bakunin’s political journalism - M. A. Fedotov (Проблемы постсоветского пространства)
M.A. Bakunin is known all over the world as one of the founding fathers and major theorists of anarchism. His ideas of social revolution and future stateless society have become the subject of reflection for succeeding generations of revolutionaries, theorists and researches. However, some aspects of Bakunin’s creative legacy haven’t been explored yet. The article is dedicated to the analysis of the issue of Russian-German relations and their reflection in Bakunin’s political journalism. Both famous and little known works were analyzed. The author concludes that Bakunin considers Germany as embodiment of the idea of the State. This idea, in turn, is antagonistic to the thinker’s global goal — the social revolution.